Od siedzącego do aktywnego trybu życia: zmieniające się modele aktywności ruchowej u dzieci - Hirsh, Alon (Studia Edukacyjne, 2017)
Physical activity is defined as body movement produced by muscle action that increases energy expenditure. The lifestyle of hominids/humans included physical activity. The way of life associated with hunting, gathering, and agriculture. During the Hellenic Age (336-30 B.C.), Sports were considered “physical training for health”, and agonal (competitive) gymnastics were highly regarded. For Romans, some body movements served the purpose as preparation for war and the military. Our young people live in a social and physical environment that makes it easy to be sedentary. The benefits of physical activity for children, though seemingly obvious. Physical activity can reduce anxiety, feelings of stress. A reduction in sedentary behavior can be achieved with minimal financial or time requirements. Positive experiences with physical activity at a young age help lay the basis for being regularly active throughout early and later adulthood. Recommended physical activity guidelines differ according to age group. Performance of a wide variety of physical activities is important for refining already learned motor skills. Sport participation, appropriately directed, could be involved in the development of character, work discipline, teamwork, fair play, and other socially approved characteristics.